On the Magneto-Heat Coupling Model for Large Power Transformers (Communications in Computational Physics, 2017)
This paper studies the magneto-heat coupling model which describes ironloss of conductors and energy exchange between magnetic field and Ohmic heat. Thetemperature influences Maxwell's equations through the variation of electric conductivity,while electric eddy current density provides the heat equation with Ohmic heatsource. It is in this way that Maxwell's equations and the heat equation are coupledtogether. The system also incorporates the heat exchange between conductors andcooling oil which is poured into and out of the transformer. We propose a weak formulationfor the coupling model and establish the well-posedness of the problem. Themodel is more realistic than the traditional eddy current model in numerical simulationsfor large power transformers. The theoretical analysis of this paper paves a wayfor us to design efficient numerical computation of the transformer in the future.